Young Filipinos’ Attitudes Towards Counterfeit Products: A Descriptive Study on Attitudes and Perceptions: A Study by the IP Academy of the Intellectual Property Office of the Philippines - Bumanglag, Ma. Liezel (Animo Repository, 2022)
The prevalence of counterfeit goods is a problem that is affecting different countries, posing threats to individuals, businesses, and economies. Given that the Philippines is characterized by its largely young population, this study aims to describe the perceptions and attitudes of young Filipinos toward counterfeit goods, with the hope of using this data to assist the Intellectual Property Office of the Philippines (IPOPHL) in its fight against counterfeits. Specifically, this study aims to describe the demographic characteristics of young Filipinos who have bought counterfeit goods; to describe the frequency and willingness of young Filipinos to buy counterfeit goods; to identify their common reasons for buying counterfeit goods; and to determine possible reasons to make them stop buying. This study utilized a quantitative descriptive design through an electronic survey to answer the research objectives. A total of four hundred and six (406) respondents with an age range of 15 to 30 years old, who have bought at least one counterfeit good, were included in the study. The results showed that the respondents can easily spot counterfeit goods by their quality and price and they do not regularly purchase counterfeit goods. The top three (3) counterfeited goods mostly purchased by young Filipinos are apparel/accessories, footwear, and handbags/ wallets. In addition, the results showed that online selling applications make up the majority of where these counterfeit goods are being bought from. As for the overall attitudes of young Filipinos on counterfeit goods, the study revealed that although most respondents buy counterfeit goods voluntarily and by personal choice, they believe that buying counterfeit goods does not improve their social and professional image, does not excite their consumption appetite, and it poses danger to their well-being. Furthermore, the results suggested that young Filipinos believe that since counterfeit products are easily accessible everywhere, especially in the advent of online apps and social media platforms, awareness campaigns geared towards discouraging people from buying counterfeit goods are needed, along with brand-related measures.